The Use of Berlin Heart EXCOR VAD in Children Less than 10 kg: A Single Center Experience - Di Molfetta, Arianna; Gandolfo, Fabrizio; Filippelli, Sergio; Perri, Gianluigi; Di Chiara, Luca; Iacobelli, Roberta; Adorisio, Rachele; Favia, Isabella; Rizza, Alessandra; Testa, Giuseppina; Di Nardo, Matteo; Amodeo, Antonio (Frontiers in Physiology, 2016)
Objective: Despite the improvement in ventricular assist device (VAD) therapy in adults and in adolescents, in infant population only Berlin Heart EXCOR (BHE) is licensed as long term VAD to bridge children to Heart Transplantation (HTx). Particularly demanding in terms of morbidity and mortality are smallest patients namely the ones implanted in the first year of life or with a lower body surface area. This work aims at retrospective reviewing a single centre experience in using BHE in children with a body weight under 10kg. Methods: Data of all pediatric patients under 10kg undergoing BHE implantation in our institution from March 2002 to March 2016 were retrospectively reviewed Results: Of the 30 patients enrolled in the study, 53% were male, 87% were affected by a dilated cardiomyopathy with an average weight and age at the implantation of 6.75±2.16Kg and 11.57±10.12 months, respectively. Three patients (10%) required a BIVAD implantation. After the implantation, 7 patients (23%) required re-intervention for bleeding and 9 patients (30%) experienced BHE cannulas infection. A total of 56 BHE pump were changed for thrombus formation (1.86 BHE pump for patient). The average duration of VAD support was 132.8±94.4 days. Twenty patients (67%) were successfully transplanted and 10 patients (33%) died: 7 for major neurological complication and 3 for sepsis. Conclusion: Mechanical support in smaller children with end stage heart failure is an effective strategy for bridging patients to HTx. The need for BIVAD was relegated, in the last years, only to restrictive cardiomiopathy. Further efforts are required in small infants to improve anticoagulation strategy to reduce neurological events and BHE pump changes.